Cuticular transpiration is not affected by enhanced wax and cutin amounts in response to osmotic stress in barley. Issue 4 (3rd July 2022) - Shellakkutti, Nandhini; Thangamani, Priya Dharshini; Suresh, Kiran; Baales, Johanna; Zeisler‐Diehl, Viktoria; Klaus, Alina; Hochholdinger, Frank; Schreiber, Lukas; Kreszies, Tino
Abstract: The plant cuticle, which covers all aerial parts of plants in their primary developmental stage, is the major barrier against water loss from leaves. Accumulation of cutin and waxes has often been linked to drought tolerance. Here we investigated whether cutin and waxes play a role in the drought adaption of barley mimicked by osmotic stress acting on roots. We compared the cuticle properties of cultivated barley ( Hordeum vulgare spp. vulgare ) with wild barley ( Hordeum vulgare spp. spontaneum ), and tested whether wax and cutin composition or amount and cuticular transpiration could be future breeding targets for more drought‐tolerant barley lines. In response to osmotic stress, accumulation of wax crystals was observed. This coincides with an increased wax and cutin gene expression and a total increase of wax and cutin amounts in leaves, which seems to be a general response triggered through root shoot signalling. Stomatal conductance decreased fast and significantly, whereas cuticular conductance remained unaffected in both wild and cultivated barley. The often‐made conclusion that higher amounts of wax and cutin necessarily reduce cuticular transpiration and thus enhance drought tolerance is not always straightforward. To prevent water loss, stomatal regulation under water stress is much more important than regulation or adaptation of cuticular transpiration in response to drought.